Use of gamification for the prevention and promotion of oral health: scope review protocol (Research, Society and Development, 2022)
The objective is to conduct a review protocol to map the use of gamification for prevention and promotion of oral health in children. This is a research protocol based on JBI’s recommendations, following the checklist of the Preferred Reporting Items for Systematic and Meta-Analyses- Extension for Scoping Reviews (PRISMA) checklist. A search and data collection will be performed with the descriptors of Health Science (DeCS), Medical Subject Heading (MeSH) and in the gray literature. Two researchers will make the selection of studies independently. This review will be previously registered in the Open Science Framework (OSF) repository. Published and unpublished bibliographic materials will be considered, according to the following inclusion criteria: children (population), gamification (concept) and oral health prevention and promotion (context). Data sources will be Web of Science, BVS, PUBMED and Google academic. Two independent reviewers will develop the analysis of relevance of the articles, the extraction and synthesis of data.